Effectiveness and cost-effectiveness of a structured integrated post-pulmonary embolism follow-up care model (Attend-PE): a rationale and protocol for a multicentre clinical pre-post study - Thomas Kümler; Søren Paaske Johnsen; Anette Arbjerg Højen; Erik Lerkevang Grove; Frederikus A Klok; Bettina Wulff Risør; Stavros Konstantinides; Jan Brink Valentin; Nanna Rolving; Stine Foged Lindegaard (BMJ Open)
Introduction Patients with pulmonary embolism (PE) experience impaired functional ability and reduced quality of life long after discharge from the hospital. However, there are no structured follow-up programmes in Denmark for these patients, and there is considerable variation in practice patterns of post-PE management. No studies have investigated the effectiveness of structured follow-up care models in patients with PE. This study aims to investigate the effect and cost-effectiveness of a structured integrated post-pulmonary embolism follow-up care model (Attend-PE) compared with usual care. The Attend-PE model outlines a structured approach for in-hospital follow-up, involving group-based patient education, individual consultations and systematic use of patient-reported outcome measures to assess the patient’s physical and psychological well-being.Methods and analysis The study is conducted in Denmark, where the healthcare system is tax-funded and services are freely available for all citizens, with an expected inclusion of 2000 patients in total. A pre-post-intervention study design is used to compare outcomes in the post-implementation cohort with the pre-implementation cohort. The co-primary outcomes are (1) health-related quality of life (patient-reported outcome, PRO) and (2) adherence to medical treatment (register-based data). Secondary outcomes include PROs on disability, treatment satisfaction, self-management, anxiety, depression and work productivity, and register-based outcomes, including recurrent PE, bleeding, mortality and healthcare use. Register-based data will be assessed at baseline (date of PE event), 6 and 12 months, while PRO-data will be assessed at 6 and 12 months after the PE event. The health economic evaluation of the Attend-PE model will include a cost-effectiveness analysis and a cost-utility analysis.Ethics and dissemination The project will be conducted by the Declaration of Helsinki. In accordance with the Danish Act on Health Research Ethics §14, the study is exempt from approval. The use of survey responses in research (in anonymous form) is, however, contingent on participants’ consent, and the invitation letter therefore included information about the purpose of the study and participants’ rights to withdraw consent at any time, and that completion of the questionnaire is considered as consent to their survey data to be included in research.Study findings will be disseminated in scientific peer-reviewed journals, at national and international conferences, and for staff and decision-makers at participating hospitals and patients and relatives via the Danish Heart Association.Trial registration number Clinicaltrials.gov NCT06037096.